2018
DOI: 10.1002/pc.24809
|View full text |Cite
|
Sign up to set email alerts
|

Mode I and Mode II interlaminar fracture behavior of E‐glass fiber reinforced epoxy composites modified with reduced exfoliated graphite oxide

Abstract: In this article, Mode I and Mode II interlaminar fracture toughness, interlaminar shear strength, flexural strength and the flexural modulus of continuous unidirectional E‐glass fiber reinforced epoxy composites modified with three different graphite oxide (GO) fillers were investigated. GO was prepared through modified Hummers' method followed by thermal exfoliation at 200°C to produce exfoliated GO (EGO). Further, EGO was chemically reduced to result in reduced EGO (rEGO). Incorporation of GO and EGO fillers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The above results can be explained with the understanding of the key differences possessed by these three filler materials, GO, EGO, and rEGO. The critical characterization of the GO, EGO, and rEGO fillers was conducted, and the results were discussed in our earlier works [21]. In brief, GO fillers are observed with oxygen-containing functional groups such as hydroxyl, epoxide, carbonyl, and carboxyl groups with disordered morphology.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The above results can be explained with the understanding of the key differences possessed by these three filler materials, GO, EGO, and rEGO. The critical characterization of the GO, EGO, and rEGO fillers was conducted, and the results were discussed in our earlier works [21]. In brief, GO fillers are observed with oxygen-containing functional groups such as hydroxyl, epoxide, carbonyl, and carboxyl groups with disordered morphology.…”
Section: Resultsmentioning
confidence: 99%
“…Different variants of graphene prepared in the laboratory are used for the work. All the materials used in this work are the same as mentioned in our earlier published work [21,22]. The materials and the method description partly reproduces the wording [21,22].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tang et al reported a laminated hybrid GF/spherical h-BN/epoxy composite, made by blending-impregnation and hot compression. The as-fabricated composite exhibited considerable improvement in both vertical (3 Glass Fiber cloth (GF)/epoxy is one of the highly demanded functional composites in a wide range of applications such as aerospace, electronics, and electrical fields due to its superior chemical inertness and electrical resistivity [79]. However, these PMCs suffer from poor interfacial adhesion to the epoxy matrices causing a gradual degradation in the mechanical properties and lowering the TC [80].…”
Section: H-bn Within Hybrid Filler Configurationsmentioning
confidence: 99%